2021
DOI: 10.1002/ese3.1031
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between flow pattern evolution and vibration in 90‐degree pipeline: Bidirectional fluid‐structure interaction

Abstract: The term "flow-induced vibration" ("FIV") was first proposed in the 1970s. 1 In the petroleum, chemical, shipbuilding, and nuclear energy industries, FIV in multiphase flow has attracted much attention due to its complex interphase interactions and high instability characteristics. The application of steam boilers in the petroleum industry highlights the energy-saving technology, and the 90-degree elbow is used as the main pipeline on the main steam pipeline of the steam boiler. In the process of petroleum ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The results suggested that the maximum error of the natural frequency of the pipeline system considering the fluid–solid coupling effect is 9.66%, which proves that the model can better simulate the dynamic characteristics of the pipeline system. Liang et al (2022) examined the vibration characteristics of the elbow under two-phase flow by using the two-way fluid–solid coupling method. The results indicate that the vibration amplitude of the elbow centre is the largest, and the Y -direction corresponds to the strongest direction of the triaxial vibration.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that the maximum error of the natural frequency of the pipeline system considering the fluid–solid coupling effect is 9.66%, which proves that the model can better simulate the dynamic characteristics of the pipeline system. Liang et al (2022) examined the vibration characteristics of the elbow under two-phase flow by using the two-way fluid–solid coupling method. The results indicate that the vibration amplitude of the elbow centre is the largest, and the Y -direction corresponds to the strongest direction of the triaxial vibration.…”
Section: Introductionmentioning
confidence: 99%
“…The model established by the thermomechanical consistency framework could accurately describe the internal structure of the fluid, and the results showed that the method better described the frictional coupling mechanism between the fluid and the solid, as well as the distribution of shear stress in a non-constant fluid. Liang [23] used a simultaneous two-thread analysis method to analyze the dynamic characteristics of the elbow considering fluid-solid coupling. It elucidated the vibration variation law caused by the gas-liquid two-phase flow in the elbow.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical analysis results show that the novel MVIMD with parameters optimized by the genetic algorithm has better effects for controlling both horizontal and vertical vibration responses of pipelines. Z Liang [11] finds that the unique modal frequencies of each order are applied to the elbow to obtain different exclusive mode shapes. The evolution of the flow pattern is related to the increase in wave height, and the wave amplitude often depends on the gas-liquid superficial velocity.…”
Section: Introductionmentioning
confidence: 99%